2015
DOI: 10.1166/jnn.2015.11441
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Amorphous Cobalt-Doped Molybdenum Sulfide for Hydrogen Evolution Reaction

Abstract: In the present study, hydrogen evolution reaction (HER) by alkaline water electrolysis was conducted without using a precious metal catalyst. We synthesized an amorphous cobalt-doped molybdenum sulfide by electrodeposition using different cobalt loadings. The amorphous Co-MoSx produced was characterized by scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The cobalt doping and sulfidation procedure resulted in the successful fabrication of a candidate catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Comparison of the fabricated Co x W (1− x ) S 2 nanosheet with the state‐of‐the‐art HER electrocatalysts in terms of Tafel slope and the overpotential required to achieve current density of 10 mA cm −2 . Data from references …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the fabricated Co x W (1− x ) S 2 nanosheet with the state‐of‐the‐art HER electrocatalysts in terms of Tafel slope and the overpotential required to achieve current density of 10 mA cm −2 . Data from references …”
Section: Resultsmentioning
confidence: 99%
“…Of the many approaches to improve the intrinsic activity of TMD's catalysis, doping of another atom is believed to play a significant role in optimizing the free energy of hydrogen adsorption . As such, experimental and theoretical studies reveal that metal or chalcogen doped TMDs are more active than undoped binary ones. Particularly, Co exhibits most significant promotional effect in catalyzing HER as evidenced in FeS 2 , MoS 2 , WS x , and MoS x by lowering the free energy barrier for H adsorption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the MoS 2 nanosheets doped with various heteroatoms exhibit superior catalytic performance for the hydrogen evolution reaction (HER) [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Intorductionmentioning
confidence: 99%
“…Introducing heteroatoms into MoS 2 or WS 2 can increase the HER catalytic activity typically because of the significantly decreased Gibbs free energy of hydrogen adsorption [22][23][24]. It has been documented that forming a solid solution of M II (M=Co, Ni)WS can not only increase the HER activity but also improve the stability [25,26]. Tran et al indicated that the catalytic active sites are located at M II S cluster in the single Co-S-W phase, while the WS 2 layer functions as a coordination ligand stabilizing and tuning the catalytic performance [27].…”
Section: Introductionmentioning
confidence: 99%